W(h)ither human cardiac and body magnetic resonance at ultrahigh fields? technical advances, practical considerations, applications, and clinical opportunities. (23rd February 2015) - Niendorf, Thoralf; Paul, Katharina; Oezerdem, Celal; Graessl, Andreas; Klix, Sabrina; Huelnhagen, Till; Hezel, Fabian; Rieger, Jan; Waiczies, Helmar; Frahm, Jens; Nagel, Armin M.; Oberacker, Eva; et al.
Abstract : The objective of this study was to document and review advances and groundbreaking progress in cardiac and body MR at ultrahigh fields (UHF, B 0 ≥ 7.0 T) with the goal to attract talent, clinical adopters, collaborations and resources to the biomedical and diagnostic imaging communities. This review surveys traits, advantages and challenges of cardiac and body MR at 7.0 T. The considerations run the gamut from technical advances to clinical opportunities. Key concepts, emerging technologies, practical considerations, frontier applications and future directions of UHF body and cardiac MR are provided. Examples of UHF cardiac and body imaging strategies are demonstrated. Their added value over the kindred counterparts at lower fields is explored along with an outline of research promises. The achievements of cardiac and body UHF‐MR are powerful motivators and enablers, since extra speed, signal and imaging capabilities may be invested to overcome the fundamental constraints that continue to hamper traditional cardiac and body MR applications. If practical obstacles, concomitant physics effects and technical impediments can be overcome in equal measure, sophisticated cardiac and body UHF‐MR will help to open the door to new MRI and MRS approaches for basic research and clinical science, with the lessons learned at 7.0 T being transferred into broad clinical use including diagnostics and therapy guiding at lower fields. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This work documents and reviews advances and progress in cardiac and body MR technology at ultrahigh fields and its application in forefront research and in early clinical applications. The achievements of ultrahigh field cardiac and body MR are shown to be a powerful motivator and enabler, since the extra speed, signal and imaging capabilities may be invested to overcome the fundamental constraints that continue to hamper traditional cardiac and body MR applications at lower magnetic field strengths.